Exploring Iranian Identity: A Contrastive Analysis of Western Literary Perspectivesversus Iranian Art of Dance - Pondelíková, Ivana; Majdáková, Veronika (Acta humanitarica academiae Saulensis, 2024)
The concept of identity is currently one of the most frequently examined in cultural studies. Identity refers to the identification of an individual with a certain unit based on signs that he/she consciously or subconsciously accepts as his/her own. There are two main currents in identity research: primordialism (essentialist approach) and instrumentalism (constructivist approach). In today’s individualized society, there is a shift in emphasis from primordiality, i.e. from that side of identity that is given, permanent, inherited, fixed, to instrumentality, i.e. to such a basis of identity that a person chooses, creates, or selects. The research focuses on Iranian identity and its reflection in Western literature and the Iranian art of dance. Iran has an exceptional position in its region and influences global events with its policy. The question is what allowed the Persians to remain Persians for more than two and a half millennia. Persian identity is expressed mainly in spiritual power, poetry, and religion. The Persians gave the world poetry, miniatures, and carpets. From the point of view of production prosperity, all useless things. But that is how they express themselves. They gave the world what did not serve to make life easier but to make it more beautiful (Kapuściński, 2016, p. 153). The empirical part of the research is divided into two parts. In the first part of the research, the authors focus on expressing Iranian identity in their traditional and modern dance. The Persian “classic” is characterized by an expressive movement of the upper part of the body, delicate movements of the shoulders and palms, and eloquent facial expressions. The dance is very poetic and often depicts scenes from Persian poems. The second part of the research focuses on examining how Iranian identity is reflected in Western literature. The study of Iranian identity is based on Azar Nafisi’s Reading Lolita in Tehran (2003), who is a representative of Iranian anglophone immigrants, as well as on an unintentional tetralogy of novels by Betty Mahmoody, the author of the novels Not without my Daughter (1987) and For the love of a child (1992), her daughter Mahtob, the author of My Name is Mahtob (2013), and Moody, Mahmoody’s ex-husband and Mahtob’s father, the author of Lost without my Daughter (2013). The culture of a nation is expressed in the identity of its inhabitants, and literature and the art of dance contribute to its understanding.